Effect of post-weld heat treatment on microstructure and mechanical properties of 7055 aluminum alloy electron beam welded joint - Zheng Wang; Shaogang Wang; Chengcong Zhang; Zhiguo Wang (Materials Research Express, 2020)
The spray forming 7055 aluminum alloy is welded by electron beam welding (EBW). After welding, the single solution treatments under different temperatures and then aging treatment (STA) and the stepped solution treatment and then aging treatment (SSTA) are carried out for the welded joints respectively. The effect of different post-weld heat treatment (PWHT) procedures on the microstructure and mechanical properties of welded joints is systematically investigated. Results show that, in as-welded condition, the fusion zone mainly consists of α -Al phase, and there are some precipitated phases such as Mg _32 (Al,Zn) _49 , Al _7 Cu _2 Fe, Al _2 CuMg, and a small amount of phase MgZn _2 in weld metal. After PWHT, the continuous network structures at grain boundary disappear. There are only a few isolated particle phases at grain boundary, and many ellipsoidal η ′ phases and rod-like η phases are precipitated within grains. The mechanical property of welded joint is improved after PWHT. Compared with that of in STA condition, the strengthening effect to welded joint is more obvious after SSTA. In SSTA condition, the hardness of weld zone is close to that of base metal (BM), and the tensile strength of welded joint reaches 486.2 MPa, which is 85.6% of that of BM. There are many equiaxed dimples on the tensile fracture surface, and the joint mainly presents the characteristic of ductile fracture.